Biological properties of the intervertebral cages made of titanium containing a carbon-carbon composite covered with different polymers - Pesáková, V; Smetana, K; Sochor, M; Hulejová, H; Balík, K (Journal of materials science. Materials in medicine, 2005)
Intervertebral cages are used in orthopaedics for stabilization of injured lumbar parts of vertebral columns. Our study provides preliminary results of tests of the biological properties of titanium cages with a variously modified carbon/carbon composite (C/C) core. This core was produced from a C/C composite modified by hydrogel materials based on poly(2-hydroxyethyl methacrylate) (HEMA) enriched with 1% collagen or 35% methylmethacrylate or 30% terc-butylmethacrylamide. We evaluated the adhesion of the cells to the tested material coating using an in vitro study of the metabolic activity and cytokine production of the cells (TNF-alpha, IL-8). We studied the biocompatibility of intervertebral cages coated with different copolymers under in vivo condition and in an implantation experiment in the porcine femurs. Both in vitro and in vivo results revealed favourable biotolerance of the use system. Modification of the composite HEMA with the use of collagen seems to have a more positive effect on the new bone tissue formed around the implanted devices than HEMA copolymerized with methylmethacrylate or terc-butylmethacrylamide.
Keywords: Equipment Failure Analysis; Fracture Fixation, Internal; Foreign-Body Reaction; Joint Prosthesis; selhání protézy; poranění míchy; Spinal Fusion; testování materiálů; Spinal Cord Injuries; zvířata; protézy kloubů; titan; Swine; polymery; vnitřní fixace fraktury; Biocompatible Materials; Carbon; Polymers; Titanium; reakce na cizí těleso; Prosthesis Failure; biokompatibilní materiály; fúze páteře; Animals; uhlík; analýza selhání vybavení; prasata; Materials Testing